Pengaruh Laju Alir Dan Tegangan Pada Pengolahan Limbah Cair Pabrik Kelapa Sawit Dengan Metode Reaktor Elektrik Kontinu - Handayani, Della; Amri, Idral; Herman, Syamsu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Palm oil mill effluent continues to grow along with palm oil production in Indonesia. Palm oil mill effluent treatment has been using anaerobic ponds which are not efficient due to the require large areas of land and due to greenhouse gases because they produce CO2. Electrocoagulation is an alternative technology and advanced technology in treating palm oil mill effluent. Electrocoagulation is a method of coagulation using direct current through the electrochemical process. This research discusses the variation of voltage and flow rate using reactor methods with pollutant parameters such as biological chemical demand, chemical oxygen demand, total suspended solids and acidity (pH). The type of electrodes used is aluminum with voltage variations of 5, 7 and 9 volts and flow rate variations of 3,36; 4,32; and 7,5 L/hour. The sample used came from PTPN V Sei Galuh in Riau. The results obtained by the highest percentage of reduction in BOD were 84.76%; COD of 83.38%; TSS of 88.73% at a voltage of 9 volts and a flow rate of 3,36 L/hour. The results of this research are in accordance with the standard quality standards for palm oil mill effluent in the Minister of Environment Regulation number 5 of 2014. Keywords: BOD, COD, electrocoagulation, TSS, pH.